2018
DOI: 10.1002/hpm.2672
|View full text |Cite
|
Sign up to set email alerts
|

A healthy weight improves life satisfaction

Abstract: SummaryIn this study, we examine the effects of having a healthy weight in form of a healthy body mass index (BMI) on life satisfaction using the data from a diverse sample of 27 post‐communist transitional countries. We find that a healthy BMI significantly raises life satisfaction, while an increase in BMI reduces life satisfaction. We also find that the positive effect of a healthy BMI on life satisfaction substantially diminishes as the political and economic situation improves. Equally, the positive effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 53 publications
1
10
0
Order By: Relevance
“…This finding suggests that short term indicators of economic development, for instance, annual GDP growth, are more important in explaining life satisfaction than are long term indicators, for instance, GDP per capita. Although the positive effect of economic factors such as annual GDP growth is not in line with the Easterlin paradox (Easterlin, McVey, Switek, Sawangfa, & Zweig, ), it is in line with the results of previous studies on post‐communist countries (Gruen & Klasen, ; Habibov et al, ; Selezneva, ). Thus, economic development can a priori be more important for the less developed post‐communist countries, where objective indicators such as annual GDP growth are more important in explaining subjective wellbeing (Djankova et al, ; Guriev & Zhuravskaya, ; Habibov & Afandi, ).…”
Section: Resultssupporting
confidence: 74%
See 2 more Smart Citations
“…This finding suggests that short term indicators of economic development, for instance, annual GDP growth, are more important in explaining life satisfaction than are long term indicators, for instance, GDP per capita. Although the positive effect of economic factors such as annual GDP growth is not in line with the Easterlin paradox (Easterlin, McVey, Switek, Sawangfa, & Zweig, ), it is in line with the results of previous studies on post‐communist countries (Gruen & Klasen, ; Habibov et al, ; Selezneva, ). Thus, economic development can a priori be more important for the less developed post‐communist countries, where objective indicators such as annual GDP growth are more important in explaining subjective wellbeing (Djankova et al, ; Guriev & Zhuravskaya, ; Habibov & Afandi, ).…”
Section: Resultssupporting
confidence: 74%
“…Recent work has emphasized the role of height in explaining life satisfaction (Deaton and Arora, 2009; Denny, ; Habibov, Auchynnikava, Luo, & Fan, ; Montgomery, Netuveli, Hildon, & Blane, ; Rees, Sabia, & Argys, ; Rietveld, Hessels, & van der Zwan, ; Osika & Montgomery, ). Research on height and life satisfaction is inherently complex and interdisciplinary inasmuch as both height and life satisfaction is partly predetermined by genetics and partly by actual life conditions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Koepp, Snedden, & Levine, 2015). IOP in unhealthy weight is therefore likely to produce inequalities in opportunity for a broad range of other outcomes (heart disease, cancer, diabetes, and so on—Pi‐Sunyer, 2009), including those directly related to well‐being such as self‐assessed happiness (Habibov, Auchynnikava, Luo, & Fan, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Several previous studies have shown obesity to be related to deterioration in LS (4,5), HRQL (6-8) and severity of depression (9)(10)(11). While obesity has been correlated with welfare in the general population, there is not much data on the in uence of body composition on welfare among the non-obese adult individuals.…”
Section: Introductionmentioning
confidence: 99%